Comparative analysis on perspectives of environmental and non-environmental NGOs on solid waste management in Jos metropolis, Nigeria - Optimist Yohanna Habila (Center for Science and Technology, IAIN Surakarta, 2022)
This study aimed to make comparative analysis of perspectives of environmental and non-environmental NGOs in Jos Metropolis on key solid waste issues with a view to provide relevant data that would hopefully help in facilitating collaboration between the state and NGOs as well as between NGOs and relevant local and international development partners. Using purposive approach, 115 NGOs in the study area were identified and given the same questionnaire. The study revealed that there are just as many NGOs working in solid waste management (SWM) as there are NGOs that are not (50% each) and there was a link between the NGO categories across all of the parameters considered in the study. It also demonstrated that NGOs' organizational viewpoint on the solid waste issues examined in the study is unaffected by their orientation or primary field of activity, and that registration as a non-environmental NGO is not a disincentive to intervening the area ofÂ environment, particularly SWM. It is recommended that the state government adopts an all-encompassing approach or framework that allows for active NGO participation including all relevant stakeholders in the SWM initiatives undertaken by the responsible government agency. Similarly, local and development partners with interest in environmental protection need to assist the NGOs by partnering with them through funding, technical support, and research among other things.